A Study on the Quality Characteristics of Gongura Mutton Curry - An Ethnic Meat Product of Andhra Pradesh, India : 10.5958/2581-6616.2020.00004.3 - Indumathi, J.; Babu , A. Jagadeesh; Reddy, G. V. Bhaskar (Journal of Meat Science, 2021)
Mutton curry with gongura (Hibiscus sabdariffa L), a popular traditional Andhra Pradesh’s recipe, was prepared by using deboned  mutton chunks and spices. Evaluated the effect of three different levels(20,40 & 60% ) of gongura incorporation on the quality of  mutton curry at refrigeration temperature(4±1 0 C) for 20 days based on the proximate composition, pH, thiobarbituric acid reactive  substances (TBARS), free fatty acid value (FFA), sensory attributes and microbiological assay. Results were revealed that,on increase in  the addition gongura level in the product, the moisture, fibre and ash contents were (P
Keywords: Gongura; Mutton curry; Ethnic; Quality; Andhra Pradesh; India